2010
DOI: 10.1038/ejhg.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Familial neonatal isolated cardiomyopathy caused by a mutation in the flavoprotein subunit of succinate dehydrogenase

Abstract: Cardiomyopathies are common disorders resulting in heart failure; the most frequent form is dilated cardiomyopathy (DCM), which is characterized by dilatation of the left or both ventricles and impaired systolic function. DCM causes considerable morbidity and mortality, and is one of the major causes of sudden cardiac death. Although about one-third of patients are reported to have a genetic form of DCM, reported mutations explain only a minority of familial DCM. Moreover, the recessive neonatal isolated form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 35 publications
0
53
0
1
Order By: Relevance
“…Interestingly, it appears that, contrary to the SDHA/ SDHB/SDHC/SDHD and SDHAF2 mutants found in tumours, the SDHA and SDHAF1 mutants identified in LS and leukoencephalopathy, respectively, retain a significant complex II activity (20-60% according to the studies; Bourgeron et al, 1995;Parfait et al, 2000;Horvath et al, 2006;Levitas et al, 2010) and also show a decreased but still productively assembled complex II in mitochondria (Van Coster et al, 2003;Pagnamenta et al, 2006;Ghezzi et al, 2009). A SDHA mutant identified in a LS patient is associated with succinate accumulation, HIF1a stabilization and superoxide production , as described for the SDHB/C/D mutations in PGL/PH.…”
Section: Respiratory Chain Complexes and Apoptosis A Lemarie And S Grimmmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, it appears that, contrary to the SDHA/ SDHB/SDHC/SDHD and SDHAF2 mutants found in tumours, the SDHA and SDHAF1 mutants identified in LS and leukoencephalopathy, respectively, retain a significant complex II activity (20-60% according to the studies; Bourgeron et al, 1995;Parfait et al, 2000;Horvath et al, 2006;Levitas et al, 2010) and also show a decreased but still productively assembled complex II in mitochondria (Van Coster et al, 2003;Pagnamenta et al, 2006;Ghezzi et al, 2009). A SDHA mutant identified in a LS patient is associated with succinate accumulation, HIF1a stabilization and superoxide production , as described for the SDHB/C/D mutations in PGL/PH.…”
Section: Respiratory Chain Complexes and Apoptosis A Lemarie And S Grimmmentioning
confidence: 96%
“…It is thus conceivable that the uncoupling generated at the SDHB level may be the origin of an electron leakage associated with ROS generation and neuronal cell death. SDHA mutants appear to induce an equal SDH and SQR activity inhibition (Bourgeron et al, 1995;Parfait et al, 2000;Levitas et al, 2010) and it could be hypothesized that such SDHA mutations generate the observed superoxide production directly at the SDHA level and not between the succinate catalytic site and the CoQ-binding site.…”
Section: Respiratory Chain Complexes and Apoptosis A Lemarie And S Grimmmentioning
confidence: 99%
“…The SdhA G555E variant is observed in a number of patients, albeit with wide phenotypic variability (22)(23)(24). Symptoms range from minor muscle weakness to moderate Leigh disease to severe mitochondrial deficiency or neonatal cardiomyopathy and death.…”
Section: Aberrant Complex II Activity Associated With Neurodegenerationmentioning
confidence: 99%
“…In addition to SDH-associated tumorigenesis, constitutional complex II deficiencies caused by SDHA, SDHB, SDHD, and SDHAF1 mutations may also lead to Leigh syndrome, infantile leukodystrophies, and cardiomyopathy. 3,[17][18][19] In the current review, our aim is to report all currently known SDH mutations and define their nature and spectrum in SDHrelated tumors, including PCCs/PGLs, GISTs, RCCs, and PAs, as well as in other unusual tumors arising in SDH mutation carriers. We performed bioinformatics analysis using SIFT, Polyphen2, and Mutation Assessor and compared the results with those of SDHA/SDHB immunohistochemistry (IHC) to predict the functional impact of nonsynonymous mutations.…”
mentioning
confidence: 99%